UPPER DEVONIAN AND MISSISSIPPIAN FORAMINIFERAL AND RUGOSE CORAL ZONATIONS OF BELGIUM AND NORTHERN FRANCE: A TOOL FOR EURASIAN CORRELATIONS - Poty E.; Devuyst F.-X.; Hance L. (My University, 2006)
The radiation of early Carboniferous foraminifers and rugose corals following the Devonian-Carboniferous crisis offers the best tool for high-resolution correlations in the Mississippian, together with the conodonts in the Tournaisian, notably in the Namur-Dinant Basin. However, some of the guides are facies-controlled and an integrated approach combining biostratigraphy, sedimentology and sequence stratigraphy is critical to identify delayed entries, potential stratigraphic gaps and to avoid diachronous correlations. The main difficulty is in correlating shallow and deeper water facies at any given time. In existing zonations, the Viséan part of the scheme is always more detailed, reflecting the widespread development of shallow-water platforms in the early Viséan which created conditions more suitable for foraminifers and rugose corals over large areas. In contrast, the Tournaisian zones, less well documented, reflect unfavourable environmental conditions in the lower ramp (Dinant Sedimentation Area) and pervasive dolomitization of the inner ramp (Condroz and Namur Sedimentation Areas). Recent progress in understanding the Belgian early Carboniferous sequence stratigraphy and lithostratigraphy, and revision of the biostratigraphy of the key sections, strongly modify former biostratigraphic interpretations. Improvements mainly concern the latest Devonian, the late Tournaisian and the early Viséan. The late Devonian and the Tournaisian are equated with foraminifer zones DFZ1 to DFZ8 and MFZ1 to MFZ8 respectively. The Viséan correlates with zones MFZ9 to MFZ14. Zone MFZ15 straddles the Viséan-Namurian boundary and Zone MFZ16 is the youngest Mississippian zone. The rugose corals allow the recognition of ten zones, RC0 to RC9, covering the Strunian (late Famennian) to Serpukhovian interval. Discrepancies with former zonations are discussed. The Moliniacian Stage is emended to restore the coincidence between its base and that of the Viséan. © 2006 Cambridge University Press.
Keywords: BIOSTRATIGRAPHY; FORAMINIFERA; MISSISSIPPIAN; RUGOSE CORALS; UPPER DEVONIAN; Paleozoic::Carboniferous::Mississippian; Paleozoic::Devonian; Палеозой::Каменноугольная; Палеозой::Девонская